Ultrastructure of retinal vessels in diabetic patients. Issue 9 (September 1993) - Ishibashi, T; Inomata, H
Abstract : The ultrastructure of retinal vessels was examined in three eyes from diabetic patients and two eyes from control subjects. In some of the retinal blood vessels of each of the diabetic eyes, the endothelial cytoplasm was thin and had fenestrae. These fenestrations which were seen in both capillaries and venules, were closed by a thin diaphragm. Transendothelial channels were also observed in the endothelial cytoplasm. The tight junctions between endothelial cells were rarely altered. The junctions were open with short adherent regions in which the junctional membranes showed increased electron density. These morphological changes may account for the characteristic breakdown of the blood-retinal barrier in diabetic patients.